A Quark-Based Investigation of Isotopic Structures and Properties - Tagarev, Kantharaju; Nedko, Srinidhi (Journal of Research in Science and Engineering, 2026)
Isotopes of an element share the same atomic number, indicating they possess identical proton counts, yet they differ in atomic mass due to variations in neutron numbers. While isotopes are conventionally analyzed in terms of protons and neutrons, this paper explores an alternative perspective by examining isotopes through the lens of quark composition. Quarks, the fundamental constituents of protons and neutrons, come in six varieties: up, down, charm, strange, bottom, and top. However, only up and down quarks contribute to the formation of the stable baryons protons and neutrons that constitute atomic nuclei. This study begins by delineating the relationship between isotopes and their underlying quark structures, focusing exclusively on the stable up and down quarks. By investigating the number and arrangement of these quarks within various isotopes, we aim to uncover intrinsic patterns that correlate with isotopic behavior. Utilizing the modern periodic table as a foundational framework, we assess the elements based on their atomic number, which corresponds to their proton count, and subsequently analyze how these factors influence isotopic variations. In our comprehensive evaluation, we derive relationships concerning the counts of up and down quarks in the nuclei of isotopic elements, revealing critical insights into the stability and behavior of these isotopes. The developed formulas were rigorously tested across a range of isotopes, encompassing both lighter and heavier atomic masses, thereby ensuring the robustness of our findings. Furthermore, we critically analyze these relationships to draw hypotheses regarding the interplay between quark composition and isotopic stability, contributing to a nuanced understanding of atomic structure. Ultimately, this paper emphasizes the significance of quark-based investigations in advancing our comprehension of isotopes, suggesting that a deeper insight into quark dynamics may not only illuminate the complexities of isotopic behavior but also pave the way for future research in nuclear physics and related fields.